Innovative E-Learning Strategies in Mathematics Education: Enhancing Self-Directed Learning and Student Motivation - Khairah, Nurul; Surjono, Herman Dwi; Nurmiati, Euis (Media Pendidikan Matematika, 2025)
This study employs the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) within a Research and Development (R&D) framework to develop a Moodle-based e-learning platform for enhancing mathematics learning motivation and self-directed among 9th-grade students at SMPN 1 Kota Bima. The research addresses two key issues: (1) Indonesia's low math competency (PISA score: 366) and (2) local findings showing 60% of target students scoring below minimum standards with observed low learning autonomy.Using the ADDIE model, the platform was developed with interactive features (structured materials, automated quizzes, discussion forums, and progress dashboards). Evaluation instruments included pre-post motivation questionnaires (Likert scale), self-regulated learning rubrics, and math achievement tests. Validation by material and media experts confirmed high feasibility (88% and 82%, respectively). Quantitative analysis revealed statistically significant improvements in the experimental class: motivation increased by 13.83 points (paired t-test, p < 0.01, g = 0.72 [high]), and self-directed learning by 17.66 points (p < 0.01, g = 0.64 [moderate]), surpassing the control class. The results demonstrate Moodle’s efficacy in fostering 21st-century skills (4C) through hybrid learning, aligned with Vygotsky’s constructivism (social interaction scaffolding) and Keller’s ARCS theory (attention-relevance-confidence-satisfaction). The study contributes actionable insights for technology-mediated math education, emphasizing structured, feedback-driven, and student-centered design.